2017
DOI: 10.1021/acssuschemeng.7b00745
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-Derived Butadiene by Dehydra-Decyclization of Tetrahydrofuran

Abstract: Catalytic ring-opening dehydration of tetrahydrofuran (THF), itself a product of decarbonylation and reduction of biomass-derived furfural, yields 1,3-butadiene, an important monomer in rubbers and elastomers. It is demonstrated that dehydra-decyclization of THF with phosphorus-containing siliceous self-pillared pentasil (SPP) or MFI structure exhibits high selectivity to butadiene (85–99%) at both low (9%) and high (89%) conversion of THF. High selectivity to pentadiene and hexadiene was also obtained from 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(142 citation statements)
references
References 26 publications
(36 reference statements)
4
121
0
Order By: Relevance
“…Very recently, Abdelrahman et al 405 proposed an alternative thermochemical pathway to produce butadiene from biomass based on the dehydration of sugars to furfural, followed by decarbonylation and hydrogenation to THF and a final dehydration and decyclization step. Regarding the last catalytic step, dehydration and ring opening of THF, they compared a phosphorous-containing siliceous self-pillared pentasil sample (P-SPP) with a wide variety of catalysts, including ZSM-5, HY, Sn-Beta, ZrO 2 and silica-alumina.…”
Section: Hierarchical Zeolites In Catalytic Pyrolysismentioning
confidence: 99%
“…Very recently, Abdelrahman et al 405 proposed an alternative thermochemical pathway to produce butadiene from biomass based on the dehydration of sugars to furfural, followed by decarbonylation and hydrogenation to THF and a final dehydration and decyclization step. Regarding the last catalytic step, dehydration and ring opening of THF, they compared a phosphorous-containing siliceous self-pillared pentasil sample (P-SPP) with a wide variety of catalysts, including ZSM-5, HY, Sn-Beta, ZrO 2 and silica-alumina.…”
Section: Hierarchical Zeolites In Catalytic Pyrolysismentioning
confidence: 99%
“…Myrcene and Far are both found in nature, but can also be produced by pyrolysis of β‐pinene and microbial pathways from glucose, respectively. Although, there are new bio‐based pathways to synthesize butadiene and isoprene, myrcene and Far are made up of multiple isoprene units, which can provide different rheological properties. It was shown that bottlebrush polymers with densely packed, long side chains improve elastic properties .…”
Section: Introductionmentioning
confidence: 99%
“…Tetrahydrofuran (THF) can also easily generate 1,4-BDO, which comes from five-carbon sugars such as xylose or furfural [66][67][68][69]. Therefore, Abdelrahman et al [70] developed a novel way to synthesize BD via the catalytic ring-opening dehydration of THF, which is conducted in the presence of a solid acid catalyst with a high selectivity of 85-99% to BD at a high THF conversion of 89% ( Figure 4). These encouraging data were obtained at 400 • C with a space velocity of 0.2 s −1 .…”
Section: Catalysts 2018 8 X For Peer Review 3 Of 25mentioning
confidence: 99%
“…Synthesis of BD from THF through the intermediate 3-buten-1-ol (3B1OL), and the by-products in the decyclization of THF[70].…”
mentioning
confidence: 99%